Response to Infant Cry in Clinically Depressed and Non-Depressed Mothers - Esposito, Gianluca (2017)
Background: Bowlby and Ainsworth hypothesized that maternal responsiveness is displayed in the context of infant distress. Depressed mothers are less responsive to infant distress vocalizations (cry) than non-depressed mothers. The present study focuses on acoustical components of infant cry that give rise to responsive caregiving in clinically depressed (n = 30) compared with non-depressed mothers (n = 30) in the natural setting of the home.